Review on price, service quality and customer loyalty in fast food restaurant / Hazirah Mohammed Shaed...[et al.] - Mohammed Shaed, Hazirah; Zulkefli, Nurul Atiqah; Ngali, Norzaidah; Rahmat, Norazlina (Faculty of Hotel and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2017)
The purpose of this paper is to provide a review on customer loyalty, specifically on price and service quality in the fast food restaurants. Customer loyalty is one of the essential aspects in determining the sustainability of business. Nevertheless, the number of empirical studies looking at the price and service quality in the fast food restaurant is still lacking. Thus, to understand the phenomenon, this paper reviews the literature about the price and service quality effects on customer loyalty. It is hopes that this paper will serve as a substantial support to both academicians and marketers.